1983
DOI: 10.1038/306492a0
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of myc gene expression in HL-60 leukaemia cells by a vitamin D metabolite

Abstract: HL-60, a cell line established from a patient with promyelocytic leukaemia, responds to a variety of inducing agents by ceasing division and acquiring some of the characteristics of either granulocytes or monocytes. Among the agents so far tested, only a comparative few occur naturally in vertebrates and would appear to have significant clinical potential in the treatment of leukaemic patients. One of the most promising of these is the dihydroxymetabolite of vitamin D3, 1,25(OH)2D3. This compound circulates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
157
0
1

Year Published

1986
1986
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(165 citation statements)
references
References 19 publications
7
157
0
1
Order By: Relevance
“…For instance, 1,25D 3 has been shown to down-regulate the expression of the c-myc proto-oncogene (Reitsma et al, 1983;Brelvi and Studzinski, 1986) and up-regulate c-jun and c-fos genes (Muller et al, 1985;Kolla et al, 1994;Kovary and Bravo, 1991), apparently related to the antiproliferative and pro-di erentiation e ects of 1,25D 3 on these cells. Although it has been shown that these e ects are separable Studzinski et al, 1997), are associated with modulation of the expression of several other genes such as mad (Wang et al, 1997b) and p27 Kip1 1997a), and are believed to be mediated by the activation of the nuclear receptor VDR (Haussler and Norman, 1969;Holick et al, 1971), the details of how 1,25D 3 controls cell proliferation remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, 1,25D 3 has been shown to down-regulate the expression of the c-myc proto-oncogene (Reitsma et al, 1983;Brelvi and Studzinski, 1986) and up-regulate c-jun and c-fos genes (Muller et al, 1985;Kolla et al, 1994;Kovary and Bravo, 1991), apparently related to the antiproliferative and pro-di erentiation e ects of 1,25D 3 on these cells. Although it has been shown that these e ects are separable Studzinski et al, 1997), are associated with modulation of the expression of several other genes such as mad (Wang et al, 1997b) and p27 Kip1 1997a), and are believed to be mediated by the activation of the nuclear receptor VDR (Haussler and Norman, 1969;Holick et al, 1971), the details of how 1,25D 3 controls cell proliferation remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of activation mechanisms of this gene have been found in various tumors (24), in sensitive response to mitogen treatment (7,19,23,31), and following in vitro-induced cell differentiation (7,37). Several possible control mechanisms of the normal c-myc gene involving a transcriptional repressor (26) or emphasizing the importance of RNA stability or turnover (4, 9, 10) have been proposed.…”
mentioning
confidence: 99%
“…Also, the proliferation of number of epithelially derived cancer cells (e.g., mammary, prostate and colon) is inhibited in culture by 1a,25(OH) 2 D 3 (Haussler et al, 1998). This e ect in neoplastic cells may be related to the reported ability of liganded VDR to arrest cells at the G 1 stage by in¯uencing cell cycle regulatory proteins, such as p21 and p27, to control cell growth factors such as c-myc (Reitsma et al, 1983;O'Connell and Simpson, 1995), c-fos (Candeliere et al, 1996) and IEX-1 (Kumar et al, 1998), or to elicit apoptosis by Figure 5 VDRE/RXRa heterodimer formation is required for the DNA-protein interaction. Electrophoretic mobility shift assay was performed using a nity puri®ed full-length human vitamin D receptor (hVDR) and human retinoic acid X receptor a (hRXRa) expressed in E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D 3 is anti-proliferative and promotes di erentiation in several cell lines such as HL60 (Reitsma et al, 1983), neuroblastoma , osteoblast (Wu et al, 1997) and HaCaT (Haugen et al, 1996) cell lines. Vitamin D 3 appears to a ect dramatically the maturation and functions of certain normal and neoplastic epithelial cells (Berger et al, 1988;Giuliano et al, 1991;Mehta et al, 1997;Saunders et al, 1993;Peehl et al, 1994).…”
Section: Discussionmentioning
confidence: 99%